A NOVEL WEARABLE HUMIDIFIER SPECTACLES FOR DRY EYES SYNDROME - Krishna, Nanditha; D, Angel Monica.; M.V, Harshitha; S, Supritha. (The journal of contemporary issues in business and government, 2021)
Tears are necessary for maintaining the health of the front surface of the eye and for providing clear vision. Dry eye syndrome (DES) or keratoconjunctivitissicca (KCS) is a common disorder where a person doesn't have enough quality tears to lubricate and nourish the eye. Dry eye is a common and often chronic problem, particularly in older adults. There are lot of consequences related to this disease such as ocular surface and tear film problem, age and gender, indoor environment, and computer vision syndrome (CVS).In this paper, we propose a novel idea to design a prototype of a wearable humidifier glasses for patients suffering with Dry Eye Syndrome. The system is designed using a microcontroller, sensors such as temperature and humidity ,a mini micro pump ,and an ultrasonic transducer. The glasses are fixed with sensors to make it as an active device. The proposed system continuously monitors the dryness of the eye and can self-regulate the moisture for the eyes based on the humidity level in proximity to the eye.